Developing Yogyakarta’s Halal Tourism Potential for Strengthening Islamic Economy in Indonesia - FATKURROHMAN FATKURROHMAN (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2017)
Yogyakarta is one of famed tourism cities in Indonesia. This city offers vari- ous cultures, natural uniqueness and culture heritage which is extremely valu- able. Yogyakarta’s uniqueness and beauty boosts domestic and foreign tourists come to this city to relish Yogyakarta’s raciness. Foreign tourist from Malaysia gives high contribution in Yogyakarta tourism. In 2014, Malaysia tourist arrived to Yogyakarta approximately 25,280 which became the third largest foreign tour- ist after Netherlands and Japan. The aim of this research is to develop Yogyakarta’s big potential as halal tourism destination for strengthening Islamic economy in Indonesia. The big potential of Yogyakarta as halal tourism destination can be seen from two aspects. Firstly, sum of big Malaysia tourist to Yogyakarta is chance to implement halal tourism. Secondly, in general, halal tourism will encourage Islamic economy growth in Indonesia. I use method of analysis of documents to do this research. The result of research is Yogyakarta has chance to be developed as one of halal tourism destinations in Indonesia. To sum up, Yogyakarta’s big potential as halal tourism destination must be developed to actualize sustainable halal tourism in Yogyakarta